Benefits of using a computer-aided program for anomia. Changes in the type of errors in naming and generalization of improvements. - González-Sánchez, Mercedes; Vereda-Alonso, Cristina (Taylor & Francis, 2025)
Abstract Background. Recent research has shown the effectiveness of computerized therapy in the treatment of anomia in patients with aphasia. Multisensory stimulation, the use of various types of aids for lexical access, and immediate feedback favor this type of therapy. In the present study, the Computer-assisted Anomia Rehabilitation Program (CARP2) was applied. Aims This study was designed to verify the efficacy of CARP2 in naming, to analyze the changes in terms of correct responses and types of errors according to the type of anomia, and to verify whether changes were generalized to the processes and skills involved in naming. Methods & Procedures Ten people with aphasia were treated for 25 weeks; four had lexical anomia, two phonological anomia, and four semantic anomia. Neuropsychological assessment was conducted pre- and post-treatment. Outcomes & Results The patients increased their effectiveness in naming, reducing, or modifying the type of error. Generalization effect of benefits is predominant. Conclusions The study’s findings suggest the potential efficacy of the CARP2 program. This therapy might be beneficial across anomia types, although generalization of treatment gains appears somewhat restricted in the case of semantic anomia.
https://openpolicyfinder.jisc.ac.uk/id/publication/1223?from=single_hit
Keywords: Afasia; Anomía; Neuropsicología; Aphasia; Anomia; Therapy; Computer; Neuropsychology